2009
DOI: 10.1080/07315724.2009.10719764
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal and Hormonal Effects of Magnesium Deficiency

Abstract: Magnesium (Mg) is the second most abundant intracellular cation where it plays an important role in enzyme function and trans-membrane ion transport. Mg deficiency has been associated with a number of clinical disorders including osteoporosis. Osteoporosis is common problem accounting for 2 million fractures per year in the United States at a cost of over $17 billion dollars. The average dietary Mg intake in women is 68% of the RDA, indicating that a large proportion of our population has substantial dietary M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
202
1
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 250 publications
(224 citation statements)
references
References 55 publications
4
202
1
6
Order By: Relevance
“…Bone mineral contents, densities and T scores were neither improved in women consuming , 0路9 mg/d Cu, nor exacerbated in women consuming $0路9 mg/d Cu, by the Zn plus Cu supplement. However, Cu intake might have had some effect on the Baseline 217 767 32 770 29 12路9 0路5 12路9 0路4 3路28 0路23 3路13 0路23 Year 1 181 803 36 771 31 13路3 0路6 12路5 0路4 3路50 0路25 3路18 0路23 Year 2 167 824 37 838 43 12路9 0路5 13路2 0路6 3路70 0路28 3路25 0路25 Post-year 3 150 804 34 802 37 13路0 0路5 12路4 0路5 3路73 0路28 3路30 (16) , and Mg deficiency may be a risk factor for bone loss in postmenopausal women (17) . Thus, an analysis was made of whether the negative response to Zn supplementation was greater with Mg intakes ,237 mg/d through exacerbating the negative effect of Mg deprivation on bone health.…”
Section: Resultsmentioning
confidence: 99%
“…Bone mineral contents, densities and T scores were neither improved in women consuming , 0路9 mg/d Cu, nor exacerbated in women consuming $0路9 mg/d Cu, by the Zn plus Cu supplement. However, Cu intake might have had some effect on the Baseline 217 767 32 770 29 12路9 0路5 12路9 0路4 3路28 0路23 3路13 0路23 Year 1 181 803 36 771 31 13路3 0路6 12路5 0路4 3路50 0路25 3路18 0路23 Year 2 167 824 37 838 43 12路9 0路5 13路2 0路6 3路70 0路28 3路25 0路25 Post-year 3 150 804 34 802 37 13路0 0路5 12路4 0路5 3路73 0路28 3路30 (16) , and Mg deficiency may be a risk factor for bone loss in postmenopausal women (17) . Thus, an analysis was made of whether the negative response to Zn supplementation was greater with Mg intakes ,237 mg/d through exacerbating the negative effect of Mg deprivation on bone health.…”
Section: Resultsmentioning
confidence: 99%
“…A very interesting result of this study was that the variants containing Mg slightly increased cell adhesion capacity. It is also demonstrated that Mg is closely associated with the mineralization of calcified tissues, directly stimulating osteoblast proliferation [9]. In addition to chemistry, the dimension of ceramic crystals is a factor implicated in the first phase of cell-biomaterial interactions.…”
Section: Discussionmentioning
confidence: 99%
“…In this process, Mg inhibits calcium phosphate cluster growth and stabilizes the amorphous state of bone mineral apatites [8]. Mg depletion alters bone and mineral metabolism and results in bone loss [9], and has been considered a risk factor for osteoporosis [10]. Experimental Mg deficiency in rats causes abnormalities in skeletal structure, enzyme (i.e., alkaline phosphatase) activity and bone mineralization that resemble some of those seen in several clinical bone diseases [11].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that a marked reduction of calcium causes a decrease of bone mass in rats (Rude, Singer, & Gruber, 2009). Numerous studies that have reported the beneficial effects of MKS on osteopenia and calcium homeostasis in rats with calcium deficiency A diet low in calcium (80-100 mg /day versus 800-1200 mg /day) reduced femoral BMD in rats by 12%.…”
Section: Effects Of Vitamin K2 In Rats Fed Diets Deficient In Calciummentioning
confidence: 99%
“…Magnesium deficiency reduces bone strength in the femur with no significant changes in the cortical BMD and cortical thickness (Rude, Singer, & Gruber, 2009). The administration of MKS in these rats does not alter the value of femoral BMD or the thickeness of bone tissue.…”
Section: Effects Of Vitamin K2 In Rats With Magnesium Deficiencymentioning
confidence: 99%